2015
DOI: 10.1002/aoc.3274
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐catalyzed three‐component cyclization of 2‐bromocyclohex‐1‐enecarboxylic acids with carbon monoxide and arylhydrazines leading to 2‐anilinohydroisoindoline‐1,3‐diones

Abstract: Bromocyclohex-1-enecarboxylic acids are carbonylatively cyclized with arylhydrazines or their hydrochlorides in tetrahydrofuran at 120°C under carbon monoxide pressure in the presence of a catalytic amount of PdCl 2 and 1,3-bis(diphenylphosphino) propane along with Et 3 N to give 2-anilinohydroisoindoline-1,3-diones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In an subsequent attempt, catalytic amounts (5 mol %) of different palladium salts were checked, Pd(TFA) 2 , Pd(OAc) 2 , and Pd(MeCN) 2 Cl 2 provide 1c in 57 %, 63 %, and 83 % yield, respectively (Table 1, entries 12-14). To modulate the catalytic activity of other palladium catalysts, PdCl 2 (dppp) (dppp: [1,1'-Bis(diphenylphosphino)ferrocene]) and PdCl 2 (dppe) [dppe: 1,2-bis(diphenylphosphino)ethane)] were used, but the yield of benzophenone did not increase (Table 1, entries [15][16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an subsequent attempt, catalytic amounts (5 mol %) of different palladium salts were checked, Pd(TFA) 2 , Pd(OAc) 2 , and Pd(MeCN) 2 Cl 2 provide 1c in 57 %, 63 %, and 83 % yield, respectively (Table 1, entries 12-14). To modulate the catalytic activity of other palladium catalysts, PdCl 2 (dppp) (dppp: [1,1'-Bis(diphenylphosphino)ferrocene]) and PdCl 2 (dppe) [dppe: 1,2-bis(diphenylphosphino)ethane)] were used, but the yield of benzophenone did not increase (Table 1, entries [15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Wu et al [15] reported palladium-catalyzed synthesis of phthalazinones by efficient carbonylative coupling of 2-bromobenzaldehydes and hydrazines. In 2015, Cho's group [16] reported palladium-catalyzed three-component cyclization of 2-bromocyclohex-1-enecarbox-ylic acids with carbonmonoxide and arylhydrazines give 2anilinohydroisoindoline-1,3-diones. In the following year, Perrone et al [17] developed palladium-catalyzed carbonylative coupling of α-chloroketones with hydrazines as a simple route to pyrazolone derivatives.…”
Section: Introductionmentioning
confidence: 99%